Fabrication of Silver Nanodendrites on Copper for Detecting Rhodamine 6G in Chili Powder Using Surface-enhanced Raman Spectroscopy - Luong, Truc Quynh Ngan; Dao, Tran Cao; Vu, Thi Thu; Nguyen, Manh Cuong; Nguyen, Nhu Duong (Communications in Physics, 2021)
Surface-enhanced Raman spectroscopy (SERS) is increasingly being used as a method for detecting traces of contaminants in a variety of specimens. In order to maximize SERS’s performance, the most important thing is to have highly active SERS substrates. In this report, we present a simple method for synthesizing silver nanodendrites (AgNDs) on the surface of a copper (Cu) plate using chemical deposition method. The results showed that, after fabrication, a large number of fern-like AgNDs formed on the Cu surface. These AgNDs are distributed evenly across the entire Cu surface with a relatively thick density. The prepared AgNDs were applied as SERS substrates for detecting Rhodamine 6G (R6G) in chili powders. The results showed that, using the prepared AgNDs substrates, as low as 10−10 M R6G in chili powders can be detected. This demonstrates the applicability of fabricated AgNDs as a highly active SERS substrate